Factors Associated with Type 2 Diabetes Mellitus Complications at Kitamura Clinic, Pontianak - Fira Rizky; Iskandar Arfan; Dedi Alamsyah (Indonesian Journal of Administration and Health Research (IJAHR), 2025)
Diabetes Mellitus (DM) type 2 is a lifelong disease that can cause complications in various organs. This study aims to describe the risk factors of type 2 DM with complications at Klinik Kitamura Pontianak. The research uses a cross-sectional design with an analytical survey method. The population consists of 1,309 DM type 2 patients in December 2021, with a sample of 93 patients selected through accidental sampling. Chi-square test was used for data analysis. The results show that age (p = 0.002), body mass index (p = 0.000), physical activity (p = 0.001), smoking behavior (p = 0.009), family history (p = 0.000), family support (p = 0.002), and duration of DM (p = 0.015) have significant relationships with DM type 2 complications. However, gender (p = 0.076) and education (p = 0.284) were not significantly related. It is recommended that patients with DM type 2 and complications become more proactive in seeking information about complication prevention and treatment, as well as adopt healthier lifestyles such as regular exercise, reducing smoking, taking medication regularly, and maintaining a healthy diet. Family support is also crucial in helping patients recover.Diabetes Melitus (DM) tipe 2 merupakan penyakit seumur hidup yang dapat menyebabkan komplikasi pada berbagai organ tubuh. Penelitian ini bertujuan menggambarkan faktor risiko DM tipe 2 yang mengalami komplikasi di Klinik Kitamura Pontianak. Penelitian menggunakan desain cross-sectional dengan metode survei analitik. Populasi penelitian terdiri dari 1.309 pasien DM tipe 2 pada Desember 2021, dengan sampel 93 pasien yang dipilih secara accidental sampling. Uji chi square digunakan untuk analisis data. Hasil penelitian menunjukkan bahwa usia (p = 0,002), indeks massa tubuh (p = 0,000), aktivitas fisik (p = 0,001), perilaku merokok (p = 0,009), riwayat keluarga (p = 0,000), dukungan keluarga (p = 0,002), dan lama menderita DM (p = 0,015) memiliki hubungan signifikan dengan komplikasi DM tipe 2. Sementara itu, jenis kelamin (p = 0,076) dan pendidikan (p = 0,284) tidak berhubungan signifikan. Disarankan agar pasien DM tipe 2 yang mengalami komplikasi lebih aktif mencari informasi tentang pencegahan dan pengobatan komplikasi, serta mengubah pola hidup dengan rutin berolahraga, mengurangi konsumsi rokok, minum obat teratur, dan menjaga pola makan. Dukungan keluarga juga penting untuk membantu pemulihan pasien.